Inovasi Melinjo Khas Banten menjadi Cookies Melinjo di Kelurahan Kalanganyar Kota Serang - Sari, Nadia Junita; Rosdiana, Lala; Wulan, Nawang; Ramadani, Radhia; Fajrudin, Lili (Universitas Pahlawan Tuanku Tambusai, 2025)
Melinjo (Gnetum gnemon L.) is a seed plant with great potential as a local food source in Banten; however, its utilization is still limited to emping and vegetables. This study aims to develop an innovation of melinjo processing into melinjo cookies as an effort to increase added value, expand product diversification. The method consisted of introducing the potential and benefits of melinjo, discussing business opportunities, demonstrating recipes and processing techniques, and hands-on practice by participants. The training involved 20 posyandu cadres through a participatory approach. The results showed that the community demonstrated high enthusiasm, indicated by their active involvement in producing cookies with original and cheese flavors. The products were considered suitable for consumption, had a distinctive taste, and showed promising potential for marketing with hygienic and attractive packaging. This training successfully enhanced community knowledge and skills, opened new entrepreneurial opportunities, and contributed to increasing income and preserving Banten’s culinary heritage through melinjo cookies innovation.